Lipid Peroxidation Is Associated with the Severity of Periodontal Disease and Local Inflammatory Markers in Patients with Type 2 Diabetes - Bastos, Alliny S. [UNESP]; Graves, Dana T.; de Melo Loureiro, Ana Paula; Rossa Júnior, Carlos [UNESP]; Parra Abdalla, Dulcineia Saes; Santo Faulin, Tanize do Espirito; Camara, Niels Olsen; Andriankaja, Oelisoa M.; Orrico, Silvana Regina Perez [UNESP] (Endocrine Soc, 2012)
Context: Periodontitis is the most common lytic disease of bone and is recognized as a common complication of diabetes. Lipid peroxidation (LPO) is increased in diabetes and may be related to modulation of the inflammatory response. LPO levels in patients with diabetes and periodontal disease have not been evaluated.Objective: The aim of this study was to evaluate the levels of LPO and its correlation with periodontal status and inflammatory cytokines in type 2 diabetic and nondiabetic patients.Design and Setting: This is a cross-sectional study involving Brazilian patients recruited at the State University of São Paulo.Patients: The sample comprised 120 patients divided into four groups based upon diabetic and dyslipidemic status: poorly controlled diabetics with dyslipidemia, well-controlled diabetics with dyslipidemia, normoglycemic individuals with dyslipidemia, and healthy individuals.Main Outcome Measures: Blood analyses were carried out for fasting plasma glucose, glycated hemoglobin, and lipid profile. Periodontal examinations were performed, and gingival crevicular fluid was collected. LPO levels were evaluated by measuring oxidized low-density lipoprotein (ELISA) and malondialdehyde (HPLC). Cytokines were evaluated by the multiplex bead technique.Results: LPO evaluated by malondialdehyde in plasma and gingival crevicular fluid was significantly increased in diabetes groups. Significant correlations between LPO markers and periodontal parameters indicate a direct relationship between these levels and the severity of inflammation and secretion of inflammatory cytokines, particularly in diabetic patients.Conclusion: These findings suggest an important association for LPO with the severity of the local inflammatory response to bacteria and the susceptibility to periodontal disease in diabetic patients. (J Clin Endocrinol Metab 97: E1353-E1362, 2012)